Study of the stabilizing muscles and the most frequent injuries in baseball 5 players/Estudio de los músculos estabilizadores y las lesiones más frecuentes en practicantes de béisbol 5 - Ardy Rafael Rodríguez García; David Perdomo Castro; Jorge de Lázaro Coll Costa; Fabiola del Carmen Vázquez Castañeda; Nélida Moraima Machín Quiñonez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Baseball, also called baseball or pelota, is a team sport played between two teams of nine players each. It is considered one of the most popular sports in Australia, Canada, Colombia, Cuba, Dominican Republic, Holland, Italy, Japan, Mexico, Nicaragua, Panama, Puerto Rico, South Korea, South Africa, Taiwan, United States, and Venezuela. The countries considered the powers of this sport are concentrated in America (North, Central and Caribbean) and Asia, with the European and African continents lagging behind. The study allowed evaluating the strength resistance of the stabilizing muscles in 11 baseball 5 players of the "Manuel Fajardo" University of Physical Culture and Sport Sciences. A survey of the most frequent injuries in this sport was carried out. The research was carried out with a non-experimental design of minimal control with pretest-posttest for a single group. The methods used were analytical-synthetic, survey and measurement. The Cron's alpha Cronbach's alpha coefficient was used to obtain the test-retest reliability of the internal consistency of the EVAL-MEB5 instrument. The instrument was applied to the sample in 2 measurements with time intervals of one week. The main results reveal that the most frequent injuries reported in the diagnosis were: pitcher's elbow, pitcher's shoulder, young baseball player's elbow, meniscus degeneration, tendinitis and bursitis. The instrument showed a test-retest reliability of 91 % and therefore presents a good reliability. The strength endurance capacity of the stabilizing muscles in the Supine Ulnar Bridge, Isometric Squat 900 to the wall and Trunk isometric was found to be deficient.